Effect of Lockdown,Temperature,and Humidity on the Pattern of COVID-19 in Erbil Province,Kurdistan Region, Iraq - Hwaiz , Rundk; Ali , Katan; Al-Tawil , Namir (Diyala Journal of Medicine, 2021)
Background: COVID-19 was first reported in Erbil province in Iraq on March 19, 2020. The effect of lockdown on reducing the spread of the novel coronavirus and the effect of weather conditions (air temperature and humidity) on the daily reported number of cases and death rate of COVID-19 were investigated during April to July, 2020. Objective: To investigate the effect of lock down on reducing the spread of the novel coronavirus pandemic and the effect of weather conditions (air temperature and humidity) on the daily reported number of cases and death rate of COVID-19. Patients and Methods: The data collected during three different periods, the first (total lockdown), followed by the second period of lockdown relaxation, which was followed by the third period (interrupted relaxation of lockdown) that reported hundreds of new cases daily. The real-time PCR .assay was performed on suspected COVID-19 patients according to the protocol established by the World Health Organization. Results: Temperature and relative humidity were recorded in Erbil city in Iraq. Patients’ age ranged (2-70) years old. Out of (1469) patients confirmed positive with COVID-19, 57.7% of them were males, 31.3% were females, and the rest (11%) were children. The mean number of patients per day was 32.77 during the period of interrupted relaxation lockdown which was significantly higher than in the total-lock down period (3.88 patient), and the relaxation lockdown period (1.93 patient). The mortality rate per day was 0.77 during the period of interrupted relaxation lockdown was significantly higher than the rates (0.0%) of the other periods. Moreover, increasing the temperature increased the number of confirmed cases in July while, low relative humidity significantly increased the rate of reported cases. Conclusion: The increase in the number of reported cases of COVID-19, might be related to the interruption of lockdown. Moreover, the daily reported cases and mortality rates increased by increasing the temperature from April to June.